The creative use of English in Japanese punning. Issue 2 (June 2016) - SCHERLING, JOHANNES
ABSTRACT: Japanese and English share a relatively short but intense history during which the number of English‐based loanwords in Japanese has risen to at least 10 per cent of the entire lexicon. This paper explores the creative uses of English (loan)words in Japanese punning, where homophonic, homonymic and paronymic relations between English words and Japanese phrases play a crucial role in creating amusing ambiguities that arise only due to the peculiar and extensive processes of loanword assimilation into Japanese which render them phonologically undistinguishable from 'original' Japanese words. English is thus naturalized in the Japanese language to such an extent that it can be widely and creatively applied to generate humor.